FAKTOR- FAKTOR YANG MEMPENGARUHI GENERASI Z DALAM MELAKUKAN NIATAN PEMBELIAN DI INSTAGRAM - Lova Lovena; KLEMENS WEDANAJI PRASASTYO (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
This research investigates the effect of cognitive factors (perceived control and trust), individual beliefs (trustworthiness, risk-taking propensity), and social media user traits (technical efficacy) on purchase intention on the Instagram social media application. The sample in this study were active users of social media Instagram who were included in the generation Z category. The number of samples used in this study were 449 respondents and the sampling was taken online in four major cities in Indonesia, namely Jakarta, Surabaya, Bandung and Yogyakarta. The empirical finding indicate that only trustworthiness has no significant effect on purchase intention, while perceived control, trust, risk propensity, and technical efficacy has significant effect on purchase intention. This study provides an understanding that in the context of Generation Z, trust in technology from applications such as Instagram is not considered by respondents in making purchase intentions. Future research with generation Z respondents is felt to be important to examine affective factors and group influences. The practical implications of this research reveal that business and industrial sectors must consider the Generation Z character in marketing their products through social media applications such as Instagram.